Analisis Implementasi Kebijakan Program Bantuan Pemberdayaan Masyarakat Keluarga Miskin (PPMKM) dalam Meningkatkan Kesejahteraan Masyarakat Keluarga Miskin di Kabupaten Donggala - La Samudia Dalili; Priyatna Prasetyawati (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to analyze: 1) the implementation of the Poor Family Community Empowerment Program in Donggala Regency; and 2) factors that affect the Implementation of the Poor Family Community Empowerment Assistance Program in Donggala Regency. This study uses a qualitative type of research. The population in this study is 10,748 people from poor families in Biromaru, Marawola and Tanantovea Districts who received PPMKM assistance according to 2005 data. The determination of the sample in this study uses purposive sampling where 94 people are used as samples in this study. The data analysis used is a qualitative analysis using a frequency table. The results of the study show that program communication, program implementation resources, program implementation disposition and program implementation bureaucratic structure are very decisive for the implementation of the Poor Family Community Empowerment Assistance Program in improving the welfare of poor families. Meanwhile, the dominant factor influencing the Poor Family Community Empowerment program is the role of the local government as a policy maker so that in general in this study it is stated that the implementation of policies has a significant effect on the implementation of PPMKM in improving the welfare of poor families in Donggala Regency.